PEMBERIAN PELAYANAN KESEHATAN DAN PELAYANAN RESEP OBAT GRATIS PADA MASYARAKAT DI KABUPATEN PADANG PARIAMAN - Ferilda, Siska; Rasyadi, Yahdian; Marsellinda, Elsa; Elvionita, Cindy; Agustin, Diva; Nabila, Hanifa; Aprilia, Fadhila; Azliany, Syifa; Fitriyasti, Betty; Fendri, Sandra tri Juli (Jurnal Abdimas Saintika, 2024)
This community service activity entitled providing health services and drug prescription services, whichwas carried out on November 3 2024, was carried out in 2 places in Padang Pariaman district. Thiswas carried out by starting with a patient's health examination and then providing a drug prescriptionservice. The community received 260 patients with 260 prescriptions consisting of 25 pediatric patients,120 adults and 115 elderly people. The most common diseases were osteoarthritis and gastritis with thedrugs used. for osteoarthritis, diclofenac, methylprednisolone and neurotropic vitamins, while forgastritis, ranitidine and omeprazole are often used.